Removal Method Assessment Through Reduction Algae Count in Uncovered water Reservoir (Journal of Engineering, 2007)
The Algae is considered as one of the major causes of some serious problems that occur in water plants, rivers, lakes and irrigation channels. Those problems are the unpleasant taste and odor, the clogging of waterways, and others. Hence, the algae existing extensively in any water body is considered as an obvious indication of surface water pollution. Chemical control methods were used in this research for reducing the turbidity and Algae in the laboratory using the (Jar Test). This was done by using chemical materials like Alum with concentration (10 - 50 mg/l). The percentage of the reduction in the algae was (95%) and in turbidity (94%). It is shown also that when using KMnO4, CuSO4 and Cl, each separately after adding the ideal dose of alum found before, will reduce the turbidity with ( 95% ,79.3% .95%) and algae removal of (99.2%, 100%, 99%) respectively